NASA's Space Shuttle Columbia : Quick Facts and Issues for Congress. (U.S. Congressional Research., 2004)
Provides information on NASA space shuttle Columbia, which exploded on Feb. 1, 2003, while returning to Earth from a 16-day science mission in orbit. Covers the shuttle mission, previous crew fatalities during space missions, the Columbia Accident Investigation Board report, and issues for Congress.